Neuroscience is ready for neuroethics engagement - Das, Jayatri; Forlini, Cynthia; Porcello, Darrell M.; Rommelfanger, Karen S.; Salles, Arleen; , Global Neuroethics Summit Delegates; Akter, Nargis; Rachel, Ankeny; Araki, Toshiyuki; Arie, Fumie; Asakawa, Tasia; Bennett, Allyson J.; et al. (Frontiers in Communication, 2022)
Neuroscience research has been expanding, providing new insights into brain and nervous system function and potentially transformative technological applications. In recent years, there have been a flurry of prominent international scientific academies and intergovernmental organizations calling for engagement with different publics on social, ethical, and regulatory issues related to neuroscience and neurotechnology advances. Neuroscientific activities and outputs are value-laden, they reflect the cultural, ethical, and political values that are prioritized in different societies at a given time and impact a variety of publics beyond the laboratory. The focus on engagement in neuroscience recognizes the breadth and significance of current neuroscience research whilst acknowledging the need for a neuroethical approach that explores the epistemic and moral values influencing the neuroscientific agenda. The field of neuroethics is characterized by its focus on the social, legal, and philosophical implications of neuroscience including its impact on cultural assumptions about the cognitive experience, identity, consciousness, and decision-making. Here, we outline a proposal for neuroethics engagement that reflects an enhanced and evolving understanding of public engagement with neuroethical issues to create opportunities to share ideation, decision-making, and collaboration in neuroscience endeavors for the benefit of society. We demonstrate the synergies between public engagement and neuroethics scholarship and activities that can guide neuroethics engagement.